Illumina sequencing analysis of the ruminal microbiota in high-yield and low-yield lactating dairy cows - Tong, Jinjin (PLoS One, 2018)
In this study, differences in the ruminal bacterial community between high-yield and low-yield lactating dairy cows under the same dietary conditions were investigated. Sixteen lactating dairy cows with similar parity and days in milk were divided into high-yield (HY) and low-yield (LY) groups based on their milk yield. On day 21, rumen content samples were collected, and their microbiota compositions were determined using high-throughput sequencing of the 16S rRNA gene by the Illumina MiSeq platform. During the study period, dry matter intake (DMI) and milk yield were measured daily, and milk composition was assessed 3 times per week. The results showed that the milk of the LY group tended to have higher fat (P = 0.08), protein (P = 0.01) and total solid contents (P = 0.04) than that of the HY group, while the HY group had higher ruminal propionate (P = 0.08) proportion and volatile fatty acid (VFA) (P = 0.02) concentrations. Principal coordinate analysis indicated significant differences in ruminal bacterial community compositions and structures between the HY group and LY group. The abundances of Ruminococcus 2, Lachnospiraceae and Eubacterium coprostanoligenes were significantly higher in the HY group than in the LY group. In addition, Bacteroides, Ruminococcus 2 and Candidatus-Saccharimonas were positively correlated with ruminal propionate proportion (r>0.4, P<0.05). These findings enhance the understanding of bacterial synthesis within the rumen and reveal an important mechanism underlying differences in milk production in dairy cows.